2008
DOI: 10.1002/anie.200705049
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Colloidal Superparticle Growth Through Solvophobic Interactions

Abstract: A supramolecular chemistry approach is used to make supercrystalline spherical colloidal superparticles (SPs, see picture) from nanoparticles. Detailed mechanistic studies show that the formation of the SPs is a two‐step process. The major driving force for superparticle formation is the solvophobic interaction between nanoparticle building blocks and the growth solution; fine‐tuning the interaction led to a size‐controlled synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 30 publications
2
179
1
Order By: Relevance
“…As illustrated schematically in Figure 1 b, when TOPO is partially substituted by 11-mercaptoundecanoic acid (MUA), a monolayer organic shell of a well-defi ned thickness was formed on the QD surfaces. This became apparent by examination of the self-assembled QD aggregates, each of which formed a face-centered-cubic (fcc) array of QDs [22][23][24] with a lattice parameter of 7.4 nm and a closest QD spacing of 5.36 nm (see Figure S1); this is clearly shown in Figure 1 c by the "110-lattice fringe imaging" [ 22 ] of the fcc QD array oriented in the 001 zone axis, under transmission electron microscopy (TEM). These fi gures and their enlargement (e.g., Figure) show a well-ordered particle (3.6 nm) array separated by gaps of 1.7 nm, which may be attributed to the organic coating.…”
Section: Doi: 101002/adma201104070mentioning
confidence: 99%
“…As illustrated schematically in Figure 1 b, when TOPO is partially substituted by 11-mercaptoundecanoic acid (MUA), a monolayer organic shell of a well-defi ned thickness was formed on the QD surfaces. This became apparent by examination of the self-assembled QD aggregates, each of which formed a face-centered-cubic (fcc) array of QDs [22][23][24] with a lattice parameter of 7.4 nm and a closest QD spacing of 5.36 nm (see Figure S1); this is clearly shown in Figure 1 c by the "110-lattice fringe imaging" [ 22 ] of the fcc QD array oriented in the 001 zone axis, under transmission electron microscopy (TEM). These fi gures and their enlargement (e.g., Figure) show a well-ordered particle (3.6 nm) array separated by gaps of 1.7 nm, which may be attributed to the organic coating.…”
Section: Doi: 101002/adma201104070mentioning
confidence: 99%
“…The hydrodynamic diameter (HD) of waterdispersible single QDs can range from 5-40 nm depending on the organic capping ligands. [11,12] Larger sized nanoparticle constructs (>40 nm) have been previously achieved by aggregation [13,14], by adsorbing QDs to larger particles [15], or by growing silica shells around individual QDs. [16] However, these larger constructs tend to have limitations either in their size range, their stability in aqueous solution, or in their brightness.…”
mentioning
confidence: 99%
“…However, less is known about how to fabricate nano-particles in the form of SCPs with well-controlled size and shape. Zhuang et al reported an approach which leads to synthesis of high-quality composite particles [21]. The proposed composite particles are similar in structure to the so-called colloidal superparticles that comprise metal oxide nano-particles and that experience growth controlled through solvophobic interactions.…”
Section: Different Kinds Of Resonances In Scpsmentioning
confidence: 99%